Larangan Meminang Wanita dalam Masa Iddah Menurut Mazhab Syafi`i - Endah Lakona Sitakar; Muhammad Amar Adly (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
The prohibition of proposing to a woman during her ‘iddah period constitutes an Islamic legal provision that is firmly grounded in the normative foundations of the Qur’an and fiqh. This provision aims to preserve the clarity of lineage, protect women’s dignity, and maintain order within the legal framework of marriage. This article examines, from a normative perspective, the prohibition of proposing to a woman during her ‘iddah according to the Shāfi‘ī school of law. The study employs a normative legal research method with a qualitative approach through library research, drawing upon the Qur’an, hadith, and authoritative (mu‘tabar) Shāfi‘ī fiqh texts. The findings indicate that the Shāfi‘ī school strictly prohibits explicit proposals to women during all types of ‘iddah, including ‘iddah resulting from revocable divorce (ṭalāq raj‘ī), irrevocable divorce (ṭalāq bā’in), annulment (fasakh), and death. As for indirect proposals (ta‘rīḍ), they are permitted only for women whose ‘iddah is not accompanied by a right of reconciliation, such as ‘iddah due to death and ‘iddah of ṭalāq bā’in, while remaining prohibited during ‘iddah raj‘ī. This legal ruling reflects the prudence of the Shāfi‘ī school in preventing the occurrence of invalid marriage contracts and affirms the function of ‘iddah as an instrument of Islamic legal regulation rather than merely a biological waiting period.